12.5% of all women's and 7.7% of all men's players from the 2022 and 2023 FIFA World Cups underwent a previous anterior cruciate ligament reconstruction - Diego Costa Astur; Gabriel De Melo Salgado; Marina Dal Piva; David Ken Nagata Radamessi; Edward Patrick Sinibaldi; Antonio Bezerra De Albuquerque Filho; Hassan Ahmad Hauache Neto; Leonardo Adeo Ramos; Moisés Cohen (Journal of Experimental Orthopaedics)
Abstract Purpose To evaluate the incidence of anterior cruciate ligament (ACL) reconstructions in athletes who participated in the men's 2022 and women's 2023 Federation Internationale de Football Association (FIFA®) World Cups, comparing the incidence between genders, positions and the stages reached by the teams during the competition. Methods This is a media analysis study, and data were collected from official club and FIFA® websites: a list of athletes who played during the men's 2022 and women's 2023 FIFA® World Cup, a list of athletes who already did an ACL reconstruction (ACLR) and rehabilitation before the competition, and stages from each team during the competition. Results 12.5% of the athletes in the women's competition (92 athletes) and 7.7% in the men's competition (64 athletes) underwent ACLR surgery before. When comparing positions (goalkeeper, defence, midfield and forwards), there were no statistical differences between men (p = 0.97) and women (p = 0.26). According to the competition stage, the prevalence increased from 12.5% in the group stage to 17.4% in the finals (p = 0.05) for women and ranged from 6.8% to 7.9% (p = 0.87) among men. The number of ACL revision surgeries was 18 in women players (2.4% of total, 19.4% of those operated) and 5 in men players (0.6% of total, 7.5% of those operated). No statistical difference in revision rates between men and women (p = 0.16). Conclusion In the highest football level competition in the world (FIFA® World Cup), there was no statistical difference between the number of men and women called up and who participated after ACLR, rehabilitation and return to sport (12.5% vs. 7.7%; p > 0.05). Furthermore, the incidence of ACL‐operated players belonging to each team that played in the World Cup increased from the stage of groups to the final in the female category (p = 0.05), but remained stable in the male category (p = 0.87). Level of Evidence Not applicable.